Paper cuts. (Economist, 2012)
The article looks at the decline in several countries' use of electronic voting machines, which are being replaced with internet voting. Security concerns about the machines, such as the inability to verify electronic tallies or check for faults and the lack of a paper trail, are discussed. Canada, Australia, and the U.S. are noted as countries where some form of online voting is occurring in 2012. Topics include preventing voter fraud and hacking, errors on paper ballots, and postal voting.